MANAGERIAL ASPECTS OF TRAINING ELECTRICAL POWER SUPPLY SPECIALISTS IN THE CONTEXT OF DECENTRALIZATION AND “GREEN” TRANSITION - Potapskyi, Pavlo; Harasymchuk, Igor; Vusatyi, Mykola; Pecheniuk, Andrii (Public Management and Policy, 2025)
This article presents a comprehensive study of the management aspects necessary for modernizing the training of engineering personnel specializing in the “Power Supply” discipline, amidst unprecedented transformational challenges. These challenges are determined by the decentralization of the national energy system and the acceleration of the global “green transition,” which fundamentally alters the specialist’s professional profile. Focusing on the critical need for entirely new competencies, the paper structurally covers and analyzes four key management areas of university activity: educational content, material and technical resources, human capital, and interaction with industry. Based on the application of systemic, comparative-analytical methods and expert evaluations, sharp discrepancies between the academic offering and the rapidly changing demands of the modern energy market are identified. Management problems are analyzed in detail, including the determined factors driving the outflow of highly qualified lecturer-practitioners and the critical issue of obsolete laboratory infrastructure, which prevents quality training in technologies such as Smart Grids and distributed generation. The article justifies the need for prompt content actualization of the “Power Supply” discipline through the integration of modules dedicated to digitalization, cybersecurity, and DC power networks. Management solutions are proposed for developing a holistic structure for the modernization system, including tools for financially stimulating lecturer-practitioners and, most importantly, mechanisms for creating joint educational and research centers on a partnership basis with leading energy companies. The implementation of these recommendations will provide the industry with specialists ready to work in an innovative and technologically complex energy environment.